The roles of motion, gesture, and embodied action in the processing of mathematical concepts - Khatin-Zadeh, Omid; Farsani, Danyal; Eskandari, Zahra; Marmolejo-Ramos, Fernando (Frontiers in Psychology, 2022)
This article discusses perspective and frame of reference in the metaphorical description of mathematical concepts in terms of motions, gestures, and embodied actions. When a mathematical concept is described metaphorically in terms of gestures, embodied actions, or fictive motions, the motor system comes into play to ground and understand that concept. Every motion, gesture, or embodied action involves a perspective and a frame of reference. The flexibility in taking perspective and frame of reference allows us to embody a mathematical concept or idea in various ways. Based on the findings of past studies, it is suggested that the graphical representation of a mathematical concept may activate those areas of the motor system that are involved in the production of that graphical representation. This is supported by studies showing that when an observer looks at a painting or handwritten letters, s/he simulates the painter’s or writer’s hand movements during painting or writing. Likewise, the motor system can contribute to the grounding of abstract mathematical concepts, such as functions, numbers, and arithmetic operations.